ANALISIS PENGARUH KOMPENSASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada PT Jasa Marga (Persero) Tbk Cabang Semarang) - Ramadhanty, Shofi Rizki; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2020)
This study aims to analyze the effect of compensation and work stress variables on employee performance with job satisfaction as an intervening variable. However employee performance is the most important asset of all, there was a problem of decreasing employee performance at PT. Jasa Marga (Persero) Tbk Semarang. Research gap from the previous research also becomes the background of this research.Â The population in this study are employees of PT. Jasa Marga (Persero) Tbk Semarang using non-probability accidental sampling in sampling with the number of participant involved in this studies as much as 63 employees. Analysis of the data used in this study is descriptive and quantitative analysis methods and uses the Sobel test as a tool for testing the effects of mediation. The data processing is done using the IBM SPSS 23 program.The results of this study indicate that compensation has a positive and significant effect on job satisfaction and also a positive and significant effect on employee performance. Job stress has a negative and significant effect on job satisfaction and also a negative and significant effect on employee performance. Job satisfaction is proven to mediate the relationship between compensation and employee performance and the relationship between work stress and employee performance. With total determination test, compensation, works stress, and job satisfaction can explain 59,2% of employee performance.Â